An overview of the geology and major ore deposits of Central Africa: Explanatory note for the 1:4,000,000 map “Geology and major ore deposits of Central Africa” - (:unkn) unknown (My University, 2006)
This paper is prepared within the frameworks of IGCP Project 470 and the associated BRGM scientific project “Africa 1999–2004” to accompany the 1:4,000,000 scale map “Geology and major ore deposits of Central Africa, presented at the 20th Colloquium of African Geology in Orleans in June 2004. It incorporates geological and metallogenic data from eight countries in Central Africa (Angola, Cameroon, Chad, Central African Republic, Congo Brazzaville, Democratic Republic of Congo (DRC), Equatorial Guinea and Zambia). The map is a harmonised and geo-referenced preliminary map, based on a GIS at 1:2,000,000 scale, and focusses on the spatial and temporal distribution of selected major deposits.
Keywords: African Research